PIPING AND BALLAST PUMP SELECTION FOR A TANK CARRIER SHIP - Witanto, Yovan (UNIB Press, 2019)
Pump is a device used to move a liquid from a lower place to a higher place by giving energy to the liquid to be moved. Generally the pump is driven by a motor, turbine, engine, or the like.PT Daya Radar Utama Unit 3 Lampung company engaged in ship production or shipbuilding. On ships there is a balancing system or commonly called a ballast system which aims to balance the ship when the load is empty or full. Balancing used is in the form of sea water which is input into the ballast tank. Therefore there is a selection of pumps to adjust to the ballast reservoir used in a ship so that the time needed to fill the tank can be according to the needs. On warships carrying steel tanks, it is known that the volume of the ballast tank is1300m3with a planned time of 5 hours. From the tank volume data that has been known, the capacity of the planned ballast pump can be calculated and the capacity obtained is260m3/h, the pipe diameter prediction value is suitable for use from the value of the ballast pump capacity of 8